2014
DOI: 10.2214/ajr.13.10852
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Change of the Secretory Flow of Pancreatic Juice in the Main Pancreatic Duct: Evaluation With Cine-Dynamic MRCP Using Spatially Selective Inversion Recovery Pulse

Abstract: Cine-dynamic MRCP using spatially selective IR pulse was able to show the age-related decrease of the secretory flow of pancreatic juice in the main pancreatic duct visually and noninvasively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Age-related morphological changes such as fibrosis in the pancreas have been reported (16). Recently, an interesting report described the pancreatic functional changes with aging (17). After excluding patients with pancreatic disease, it was shown that the frequency and distance of pancreatic juice discharge was negatively related to aging by cine-dynamic magnetic resonance cholangiopancreatography (MRCP).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related morphological changes such as fibrosis in the pancreas have been reported (16). Recently, an interesting report described the pancreatic functional changes with aging (17). After excluding patients with pancreatic disease, it was shown that the frequency and distance of pancreatic juice discharge was negatively related to aging by cine-dynamic magnetic resonance cholangiopancreatography (MRCP).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the age‐related decrease in flow of pancreatic juice in the main pancreatic duct (Fig. ) has recently been visually confirmed with cine‐dynamic MRCP using spatially selective inversion recovery pulse . In a population‐based German study (SHIP) of almost 1000 healthy individuals with normal serum lipase and amylase, there was a significant 30% reduction in secretin‐stimulated output in those over 80 years old .…”
Section: Systematic Literature Review Of Age‐related Pancreatic Functmentioning
confidence: 99%
“…24 Other reports have shown the incidence of EPI in the elderly to be as high as 21.6%. 25 Torigoe et al 26 the results of which showed that duodenal fluid production after the stimulation rose markedly with increase in age, up to 43 years, and then began to decline. 28 Bicarbonate production began to increase, along with increase in age, up to 34 years of age, and then began to decline.…”
Section: E Xo Crine Fun C Ti Onmentioning
confidence: 99%
“…Torigoe et al used dynamic magnetic resonance imaging of pancreatic biliary flow to evaluate the relationship between pancreatic exocrine function and aging. A total of 53 subjects were divided into three groups based on age (<40, 40‐70 and >70 years old).…”
Section: Exocrine Functionmentioning
confidence: 99%